Metabolomic profiles of the silage digested in ruminal fermentation differentiated by various solvent extraction. - Anggraeni, Ayu Septi; Jayanegara, Anuraga; Windarsih, Anjar; Suratno,; Sofyan, Ahmad; Laconi, Erika Budiarti; Kumalasari, Nur Rochmah (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The aim of this study was to examine the solvent conditions suitable for preparing samples of total mixed ration (TMR) silage and ruminal fluid, with or without chitosan inclusion, to achieve more sensitive, specific, and repeatable analyses. Material and Methods: The metabolome contained in the sample was determined using a ultrahigh-performance liquid chromatography-high-resolution mass spectrometry quadrupole using samples in the form of TMR silage (silage with 0.5% inclusion of chitosan, silage without chitosan addition) and rumen fluid (rumen fluid containing 0.5% chitosan, ruminal fluid without chitosan) with and without the addition of chitosan, as well as three different solvent ratios: 50% water MS grade: 50% methanol (MeOH) MS grade (1), 20% water MS grade: 80% MeOH MS grade (2), and 0% water MS grade: 100% MeOH MS grade (3). Results: The TMR silage samples contained 311 metabolites, amino acid compounds predominating, followed by fatty acids and amines. Fatty acids, organic phosphate, and amines dominated the 39 metabolites found in rumen fluid samples. In the TMR silages, 100% MeOH seemed to be able to distinguish samples more effectively than other solvents; moreover, cinnamic acid, D-(+)-proline, and L(+)-ornithine were the three highest variable importance for projection values among prospective metabolite markers for silage samples. Whereas the use of a 50% MeOH to 50% water solvent ratio achieved the best discrimination results in rumen fluid samples, the three highest variable importance for projection values among prospective metabolite markers for ruminal fluid samples were triethyl phosphate, dibenzylamine, and phosphoric acid. Conclusion: 100% MeOH is able to distinguish TMR silage, while 50% MeOH to 50% water is best for ruminal fluid samples. J. Adv. Vet. Anim. Res., 12(2): 589–600, June 2025 http://doi.org/10.5455/javar.2025.l923